The United Kingdom Ministry of Defence – the Case for Followership as a key Element of Leadership Development - Neal, Derrick J.; Boutselis, P. S.; Bennett, J. (Cranfield University, 2016)
Using the Kelley (1992) Followership Style instrument this study explores the role and perceptions of Followership within the UK Ministry of Defence. In particular, within the Armed Services and the Civil Service it was apparent from the literature that only the RAF formally recognised the role of Followership within their Leadership staff development programmes, hence the research aimed to see whether this was reflected in self-perceptions of Followership Style and the extent to which it is applied within the organisation. The analysis concluded that the analysed sample (298 responses) produced an atypical profile compared to other studies that have used the instrument. The RAF showed statistically significant higher scores than the other Armed Services or the Civil Servants and scores increased with Rank/Grade. The analysis also highlighted that the individuals seemed not to be recognised as good Followers by their leaders, they appeared not to recognise their reports as good Followers and in all cases the organisation seemed not to recognise their value. These aspects provide scope for further research to better understand the organisational culture, processes and practices that appear to act as a barrier to the extraction of the benefits of having good Followers even in an area where Star Followers dominate.
Published in Strategic Management Quarterly (2015) Vol 3 Issue 4
Keywords: Leadership